Enzymatic phosphorylation of muscle glycogen synthase: a mechanism for maintenance of metabolic homeostasis. - Shulman, R G (1996)
We recently analyzed experimental studies of mammalian muscle glycogen synthesis using metabolic control analysis and concluded that glycogen synthase (GSase) does not control the glycogenic flux but rather adapts to the flux which is controlled bv the activity of the proximal glucose transport and hexokinase steps. This model did not provide a role for the well established relationship between GSase fractional activity, determined by covalent phosphorylation, and the rate of glycogen synthesis. Here we propose that the phosphorylation of GSase, which alters the sensitivity to allosteric activation by glucose 6-phosphate (G6P), is a mechanism for controlling the concentration of G6P instead of controlling the flux. When the muscle cell is exposed to conditions which favor glycogen synthesis such as high plasma insulin and glucose concentrations the fractional activity of GSase is increased in coordination with increases in the activity of glucose transport and hexokinase. This increase in GSase fractional activity helps to maintain G6P homeostasis by reducing the G6P concentration required to activate GSase allosterically to match the flux determined by the proximal reactions. This role for covalent phosphorylation also provides a novel solution to the Kacser and Acarenza paradigm which requires coordinated activity changes of the enzymes proximal and distal to a shared intermediate, to avoid unwanted flux changes.